Biomarkers of autoimmunity and beta cell metabolism in type 1 diabetes - Yang, Mei-Ling; Kibbey, Richard G.; Mamula, Mark J. (Frontiers in Immunology, 2022)
Posttranslational protein modifications (PTMs) are an inherent response to physiological changes causing altered protein structure and potentially modulating important biological functions of the modified protein. Besides cellular metabolic pathways that may be dictated by PTMs, the subtle change of proteins also may provoke immune attack in numerous autoimmune diseases. Type 1 diabetes (T1D) is a chronic autoimmune disease destroying insulin-producing beta cells within the pancreatic islets, a result of tissue inflammation to specific autoantigens. This review summarizes how PTMs arise and the pathological consequence of PTMs, with particular focus on specific autoimmunity to pancreatic beta cells and cellular metabolic dysfunction in T1D. Moreover, we review PTM-associated biomarkers in the prediction, diagnosis and in monitoring disease activity in T1D. Finally, we will discuss potential preventive and therapeutic approaches of targeting PTMs in repairing or restoring normal metabolic pathways in pancreatic islets.